Design and Implementation of Hotspot Network Login Authentication Using QR Code Based on Mikrotik - Febryan Hari Purwanto Hari; Marsidi Amin Amin (Jurnal Komputer, Informasi dan Teknologi, 2022)
Internet Hotspot networks generally use WEP/WPA/WPA2 security as user authentication so that they can login and connect to the network, but this authentication is stored on hotspot access point devices and is used for multi users so that admins cannot manage the network efficiently. Another authentication method can be using is a captative portal system that requires users to enter a username and password to use the hotspot service. Although the use of a captative portal is quite good, the use of passwords often experiences problems, namely users forget their passwords or passwords can be spread easily. For this reason, better authentication is needed which can reduce the risk of spreading login information so that it can reduce network load. so in this study we designed and implemented Hotspot Network Login Authentication Using a Mikrotik-Based QR Code by utilizing a user manager application that is already contained in the Mikrotik package and can be directly installed and run directly on the Mikrotik device without using an additional server. The system can be created by simply adding a Mikrotik routerboard RB951Ui-2HND with a built in Mikrotik access point as an access point for Hotspots and modifying the Mikrotik default login page by adding the HTML5 and Javascript Web-based QR Code feature. The test results show that the system is able to run as desired and is able to handle the given input and is able to handle user login exploits by giving error messages. SSL certificates can be generated using the Mikrotik certificate feature, even if these certificates are not publicly known.